2016
DOI: 10.1186/s12917-016-0632-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial versus intra venous contrast-enhanced computed tomography of the equine head

Abstract: BackgroundThe anatomical complexity of the horse’s head limits the abilities of radiography. Computed tomography (CT) in combination with contrast enhanced CT is used more often for diagnosing various head pathology in horses. The objective of this study was to compare intravenous and intra-arterial contrast-enhancement techniques and describe normal and abnormal contrast enhancement in the horse’s head.ResultsAll 24 horses included in the study recovered without complication from the procedures. Compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…A recent study found that all three horses with paranasal sinus cysts given contrast (two with intra‐arterial and one with i.v. protocol) showed cyst wall contrast enhancement . Thus, it is currently not clear if the variable cystic wall enhancement seen in the current study is due to variability in the structure of the cystic wall or in the timing of the post‐contrast acquisition.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A recent study found that all three horses with paranasal sinus cysts given contrast (two with intra‐arterial and one with i.v. protocol) showed cyst wall contrast enhancement . Thus, it is currently not clear if the variable cystic wall enhancement seen in the current study is due to variability in the structure of the cystic wall or in the timing of the post‐contrast acquisition.…”
Section: Discussionmentioning
confidence: 69%
“…The horses were given 400 mL of 300 mgI/mL i.v. contrast similar to that used in other studies . A recent study found that all three horses with paranasal sinus cysts given contrast (two with intra‐arterial and one with i.v.…”
Section: Discussionmentioning
confidence: 93%
“…The use of an intra-arterial route in CT studies allows administration of a low-dose of contrast in a targeted area, which represents less than 50% of the intravenous dose. Studies have shown similar degrees of soft tissue enhancement compared with systemic intravenous administration (Carmalt and Montgomery 2015;Crijns et al 2016). In MRI, different doses have been described in the literature based on empirical experiences (Ferrell et al 2002;Werpy 2007;Judy 2011).…”
Section: Computed Tomographymentioning
confidence: 99%
“…Studies have shown similar degrees of soft tissue enhancement compared with systemic intravenous administration (Carmalt and Montgomery 2015; Crijns et al . 2016). In MRI, different doses have been described in the literature based on empirical experiences (Ferrell et al .…”
Section: The Use Of Contrast Media In the Equine Headmentioning
confidence: 99%
“…; Crijns et al . ), with those suffering from pituitary pars‐intermedia dysfunction (PPID) measuring on average 2.6 ± 0.3 cm rostrocaudal length, 2.4 ± 0.26 cm laterolateral width, and 1.92 ± 0.43 cm dorsoventral height (Kolk et al . ).…”
Section: Discussionmentioning
confidence: 99%